PENGARUH EKSTRAK KULIT BUAH MANGGIS (Garcinia Mangostana Linn) TERHADAP PERISTALTIK ILEUM TERPISAH MARMOT JANTAN SEBAGAI ANTI DIARE - Zaim Anshari; Chrismis Novalinda Ginting; Linda Chiuman; Yuliani Mardiati Lubis (Fakultas Farmasi Institut Kesehatan DELI HUSADA Deli Tua, 2019)
Objective: to determine the effect of mangosteen peel extract (Garcinia mangostana Linn) on ileal peristalsis separate male guinea pigs as diarrhea. Results: t-independent test, the difference: Contraction of ileum Acethlcholin with Atropine + Acethylcholin is 6.333 compared to Acethylcholin with extract + Acethylcholin is 8,500 with ANOVA test P value meaning the difference between the two contractions of the ileum is significant. The t-independent test results are the difference: Contraction of ileum Histamine with Diphenhidramine + Histamine is 8.333 compared to Histamine with extract + Histamine is 10.833 with ANOVA test P value meaning the difference between the two contractions of the ileum is significant. The results of the t-independent test are the difference: Contraction of the Barrium ileum with Papaverine + Barrium is 2,500 compared to the contraction of Barrium ileum with extract + Barrium is 2,500 with ANOVA test P value meaning that there is no difference between the two contractions of the ileum. From the three experimental groups, it was concluded that the extract worked similar to Papaverine. Cecilia's study, fruit skin extract can be used as diarrhea in Diare Effect of Mangosteen Ethanol Extract of Oleum ricini-induced Webster Swiss Mice.